Christobiography memory, history, and the reliability of the Gospels - Keener, Craig S. 1960- (Grand Rapids Eerdmans Publishing Co, 2019)
"The canonical gospels are ancient biographies, narratives of Jesus's life. The authors of these gospels were intentional in how they handled historical information and sources. Building on recent work in the study of ancient biographies, Craig Keener argues that the writers of the canonical gospels followed the literary practices of other biographers in their day. In Christobiography he explores the character of ancient biography and urges students and scholars to appreciate the gospel writers' method and degree of accuracy in recounting the ministry of Jesus. Keener's Christobiography has far-reaching implications for the study of the canonical gospels and historical-Jesus research. He concludes that the four canonical Gospels are historically reliable ancient biographies."--Dust jacket
Part 1. Biographies about Jesus ; Not a novel proposal ; Examples and development of ancient biography ; What sort of biographies are the gospels? ; What did first-century audiences expect of biographies? -- Part 2. Biographies as history ; Biographies and historical information ; What historical interests meant in antiquity ; Luke-Acts as biohistory ; Sources close to the event -- Part 3. Testing the range of deviation ; Case studies : biographies of recent characters use prior information ; Flex room : literary techniques in ancient biographies -- Part 4. Two objections to gospels as historical biographies ; What about miracles? ; What about John? -- Part 5. Memories about Jesus : memories before memoirs ; Memory studies ; Jesus was a teacher ; Oral tradition, oral history ; The implications of this study.
Includes bibliographical references and index
Keywords: Jesus Christ -- Historicity; Bible -- Criticism, interpretation, etc; Classical biography -- History and criticism; Biography as a literary form; Jesus Christ; Bible; Classical biography; Historicity of Jesus Christ; Criticism, interpretation, etc